Pengaruh Kepemilikan Manajerial, Komisaris Independen dan Kualitas Audit terhadap Integritas Laporan Keuangan - Rasidin, Adela Mei Putri; Hariyono, Anwar (Journal of Culture Accounting and Auditing, 2024)
This study aims to examine the effects of managerial ownership, independent commissioners, and audit quality on the integrity of financial statements. Using purposive sampling, the study focuses on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) during 2019–2022. A total of 195 financial statements from 52 companies were analyzed using descriptive statistics and multiple linear regression, with hypothesis testing conducted via SPSS. The findings reveal that managerial ownership and audit quality do not significantly affect the integrity of financial statements. In contrast, independent commissioners have a significant positive impact on financial statement integrity. These results highlight the critical role of independent commissioners in fostering transparent and reliable financial reporting. However, the low managerial ownership in the studied companies may limit the influence of this variable on decision-making and financial reporting quality. The study contributes to the literature on corporate governance by emphasizing the importance of independent oversight in improving financial reporting integrity. Future research is encouraged to explore other variables and broader contexts to provide a more comprehensive understanding.